The association between TNF-alpha and erectile dysfunction complaints - Matos, G. [UNIFESP] (2013)
Inflammatory markers like tumour necrosis factor-alpha (TNF-) have been related to erectile dysfunction (ED) and may interact with other cardiovascular risk factors such as obstructive sleep apnoea syndrome (OSAS). the aim of this study was to examine the inflammatory, metabolic and hormonal profile of men with or without ED complaints and/or OSAS recruited through the Epidemiologic Sleep Study (EPISONO). A sample of 363 men completed sexual questionnaires for ED and had physical and blood examinations. OSAS was evaluated by polysomnography and clinical assessment. the blood samples were used for determination of TNF-, interleukin-6, leptin, cholesterol and fractions, triglycerides, homocysteine, glucose and hormonal levels. After controlling for confounding factors, men with ED complaints presented higher systolic blood pressure and TNF-, independent of OSAS. Significant interaction between ED and OSAS was only observed for neck circumference, which was higher in ED men with OSAS than men with OSAS without ED and men with ED without OSAS. Binary logistic regression showed that the predictor factors for ED were age >43years, myocardial infarction events, TNF- and systolic blood pressure. Finally, a receiver-operating characteristics curve suggested a cut-off point of 9.95pg/mL for TNF- with sensitivity of 60% and specificity of 59% in men with ED complaints. Furthermore, there was a significant association between high levels of TNF- (>9.95pg/mL) and the presence of ED complaints. the results showed that there was an association between TNF- levels and ED complaints in men independent of OSAS.